Ethics, language and tradition: essays on philosophy of Rajendra Prasad - Kar, Bijayananda (Indian Council of Philosophical Research, 2009)
Papers presented at the National Seminar on 'The Philosophy of Rajendra Prasad', held at Pondicherry in 1994